Effectiveness of Hand-Eye Coordination, Strength of Fingers and Concentration on Ability Passing Over A Volleyball Game - Mahmudin; Fikri, Aprizal; Satria, M. Haris; Muslimin (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2025)
This study aims to determine the influence of eye-hand coordination, finger strength, and concentration on the ability to pass up in volleyball in students who participate in extracurricular activities at MTs Negeri 1 Prabumulih. The research uses an experimental method with a 2x2x2 factorial design. The research sample consisted of 60 students selected using a purposive sampling technique from the volleyball extracurricular student population. Data collection was carried out through a series of tests, including: (1) eye-hand coordination test using the ball wall pass test, (2) hand finger strength test with hand dynamometer, (3) concentration test using grid concentration test, and (4) upper passing ability test using brady volleyball test. The data was analyzed using a three-track ANOVA with a significance level of α = 0.05. The results showed that: (1) there was a significant influence between eye-hand coordination on upper passing ability (F_hitung = 15.32 > F_tabel = 4.08), (2) there was a significant influence between hand finger strength on upper passing ability (F_hitung = 12.45 > F_tabel = 4.08), (3) there was a significant influence between concentration level on upper passing ability (F_hitung = 10.78 > F_tabel = 4.08), and (4) there was a significant interaction between the three variables on the upper passing ability (F_hitung = 8.92 > F_tabel = 4.08). The conclusion of this study is that eye-hand coordination, finger strength, and concentration jointly or partially have a significant influence on the upper passing ability in volleyball games in extracurricular students of MTs Negeri 1 Prabumulih.